Produksi Akuakultur dan Dampak Nutrifikasi Perairan Danau Tondano - Meilona Priskila Rawung; Indra R. N. Salindeho; Sipriana Tumembouw (Sam Ratulangi University, 2014)
This study was conducted to determine the level of aquaculture production Tondano and determine the impact of the production level of the waters of Lake Tondano nutrifikasi . The data collected in this study , consisting of primary data and secondary data . Production data obtained from the questionnaire and interviews to farmers fish there , as well as data obtained from the Department of Fisheries and Village Head Office . Water sampling to determine levels of phosphate in the waters of the lake . Water sampling conducted on six (6 ) locations: Village Ranomerut , Eris Village , Village Paslaten , Leleko Village , Village and Village Paleloan Toulour . Sampling was conducted at six (6 ) points to pay attention to the position of the inlet and outlet of the waters of Lake Tondano . Tondano aquaculture production in 2014 was estimated at 1222.12 tons / year . Number KJT operated as many as 978 units . There was a decrease in aquaculture production annually over a period of 2001 - 2014. Followed by the declining number of KJT on Lake Tondano . Phosphates were donated to the waters of fish farming activities from the rest of the feed pellets . The content of orthophosphate in the waters of Lake Tondano of 0.06 mg / l means the waters of the lake are in a safe condition Tondano not pass the specified limits ( PP RI No. 82 of 2001 ) . The decline in aquaculture production decline followed Tondano phosphorus content in Lake Tondano . Another factor that is expected to also affect the amount of water hyacinth around the lake so that the phosphorus content is also on the wane . keywords : Lake Tondano, Production, Nutrification